SOLAR ARRAYS - GREGORY NOEL T; SCHMIDT JASON Z; DOUGLAS MARK V; SPENCE BRIAN R; SORENSEN PETER; WHITE STEPHEN F; TAKEDA RONALD S (2009)
A solar array including a solar array assembly, hub assembly, and wing assembly.